Plan de comunicación local para la inspectoría “Notre Dame du Perpétuel Secours” de Las Hijas de María Auxiliadora en Haití - Pierrette Louijuste, Marie (2015)
This qualified work "Plan of communication for the Province Notre Dame du Perpétuel Secours in Haiti”, translates the will, the desire of the congregation salesian of endowing every province of a coordination of the communication; her function is to encourage the communication with optics educommunicative according to the salesian’s charisma My work is part of a world process of the Institute of the FMA orientated to the: “Study, to the research and offer of orientations and of concrete ways concerning the culture of the communication from an educational optics and in dialog with the different areas. It is also an expression of the dialog realized in the meetings Interareas to continental level with the Coordinators of Social Communication of all the provinces of the world, who have contributed their reflection and offers in order that it could be translated into the practice in the educational Communities". (GONG, 2012, pág. 5). For this reason, the plan is articulated around the world and regional Plan of the ECOSAM executing strategies of the institutional communication with three axes formation, information and production. The longing for my province is that during and after the execution of this plan, every member of the Salesian’s family in Haiti has conscience of the importance of the communication in our Institute; we will creating the communicative culture inside our educational communities until salesian fma giving life to Educomunicación's career inside the top institutions in Haiti and after the Salesian’s University; this one is my dream … I am a daughter of Don Bosco